Impact of pubertal timing on growth progression and final height in subjects affected by RASopathies - Tamburrino, Federica; Mazzanti, Laura; Gibertoni, Dino; Schiavariello, Concetta; Perri, Annamaria; Orlandini, Eleonora; Rossi, Cesare; Tartaglia, Marco; Lanari, Marcello; Scarano, Emanuela (Frontiers in Endocrinology, 2025)
BackgroundRASopathies, including Noonan syndrome and related disorders, are multisystem conditions caused by mutations in various genes encoding proteins involved in the RAS/MAPK signaling pathway resulting in increased signal flow. They are clinically characterized by failure to thrive, facial dysmorphisms, congenital heart defects, lymphatic malformations, skeletal anomalies, and variable cognitive impairment, with variable prevalence in the different conditions and subtypes. Pubertal development, which affects growth and final height, is often delayed in Noonan syndrome patients, though not universally. This study aimed to evaluate the timing and progression of puberty and its impact on growth and final height in patients with RASopathies.Subjects and methodsA retrospective longitudinal study was conducted involving 103 patients with molecularly confirmed RASopathies. A subgroup of 40 patients who had completed pubertal development was analyzed. Anthropometric, hormonal (FSH, LH, estradiol/testosterone), and radiological data were collected.ResultsAmong the 40 patients who had completed puberty, 75% had a diagnosis of Noonan syndrome. The median age at pubertal onset was 11.8 years in males and 13.2 years in females. Delayed puberty was observed in 27.8% of patients, with a higher incidence in females. Median final height was significantly lower in those with delayed pubertal onset compared to those with normal development (p < 0.01). No significant differences in final height were observed between patients with growth hormone deficiency treated with growth hormone and those who were untreated.ConclusionsDelayed pubertal onset negatively impacts final height in patients with RASopathies, with inadequate pubertal catch-up growth being a common outcome. While most patients initiate puberty spontaneously, careful monitoring of growth and pubertal progression is crucial to optimize therapeutic interventions and improve final height outcomes.